TRIZ IN READING A LITERARY TEXT (IN THE EXAMPLE OF THE WORK "KYS" BY T. TOLSTAYA) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
This article highlights the methods and techniques for reading literary texts. Especially TRIZ techniques: A three-part diary and a two-part diary.